Case Report of Treatment of a Patient with Bipolar II Disorder through Cognitive Behavioral Therapy Based on the Emotion-Goal Detachment - Fatemeh Zadehmohamadi; Faramarz Sohrabi; Emad Ashrafi; Jamal Shams (Fasa University of Medical Sciences, 2021)
Background & Objective: Bipolar disorder (BD) is a severe mood disorder. In this study adjunctive psychotherapy of cognitive-behavioral therapy based on emotion-goal detachment was developed and used to treat a patient with bipolar II disorder. Case Report: A 24-year-old girl, who was diagnosed with bipolar II disorder participated in this study. When she was receiving pharmacotherapy, she went to a psychotherapy clinic and complained about depression symptoms. Her depression symptoms, matched the major depressive disorder (MDD) in accordance with DSM-IV-TR. She also complained about anxiety about her presence at the university. Results: She participated in 18 weekly sessions of The Emotion-Goal- detachment -Based CBT along with pharmacotherapy. She regulated and pursued her goals during the therapy. At the end, she showed no symptoms of MDD in accordance with DSM-IV-TR criteria. Conclusion: The proposed CBT model was meant to mitigate the effects of emotions on goal pursuit so that it will not be affected by emotional dysregulation.